2014
DOI: 10.2147/vmrr.s62775
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of respiratory route as a viable portal of entry for Salmonella in poultry

Abstract: With increasing reports of Salmonella infection, we are forced to question whether the fecal-oral route is the major route of infection and consider the possibility that airborne Salmonella infections might have a major unappreciated role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 124 publications
(268 reference statements)
0
13
0
Order By: Relevance
“…Several studies have indicated that this method does not alter hatchability, improves intestinal health, and favors microbial diversity ( 3 5 ). Furthermore, in ovo delivery of probiotics may have a significant impact in commercial poultry because hatching cabinets represent one of the first potential sources of pathogenic enterobacteria ( 6 , 7 ). Avian pathogenic Escherichia coli (APEC) may also penetrate the shell ( 8 ) or can be vertically transferred ( 9 ), causing significant mortality during the first week ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have indicated that this method does not alter hatchability, improves intestinal health, and favors microbial diversity ( 3 5 ). Furthermore, in ovo delivery of probiotics may have a significant impact in commercial poultry because hatching cabinets represent one of the first potential sources of pathogenic enterobacteria ( 6 , 7 ). Avian pathogenic Escherichia coli (APEC) may also penetrate the shell ( 8 ) or can be vertically transferred ( 9 ), causing significant mortality during the first week ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…In other poultry, different respiratory sites are known to house distinct bacterial communities that develop with age (26,27,31,32), but the contribution of these communities to poultry health is largely unknown. Of particular interest is the microbiota of the upper respiratory system (the nasal cavity and the trachea), as these sites are among the first points of contact for airborne bacteria, including aerosolized fecal bacteria (33). Understanding how upper respiratory microbiota develops alongside gastrointestinal microbiota is critical to the development of effective interventions against transmission of performance-inhibiting microorganisms and to improve poultry health and productivity.…”
mentioning
confidence: 99%
“…According to Linder & Sisson (1994) and Corley et al (2012), in the mammalian lung most pathogens and particulates are trapped before they reach the alveoli, thus the arrangement of the airways constitutes a non-specific defence system. Kallapura et al (2014) observed that infections of the avian respiratory system predominantly occur in the caudal air sacs because inhaled air loaded with foreign matter flows directly to the caudal air sacs (Fig. 3A,E).…”
Section: Functional Efficiency Of the Avian Respiratory Systemmentioning
confidence: 97%
“…In pulmonary attacks, pathogens may disseminate from there to other parts of the body (Bosch et al, 2013;Koppen et al, 2015;Hakansson, Orihuela & Bogaert, 2018). In chickens (Gallus gallus variant domesticus), Kallapura et al (2014) observed that the respiratory tract may have been underestimated as a portal of entry of Salmonella infections. For gas exchange by passive diffusion, the BGB of lungs of birds is exceptionally thin Maina, 1989Maina, , 1993Maina, , 2005Maina & West, 2005): the BGB considerably exposes the body to attacks and injuries by pathogens and foreign agents (Hendrickson & Matthay, 2013;Clementi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation